Optimal Land Use and the Allocation of Endogenous Amenities - Wilbert Grevers; Anne van der Veen (European Regional Science Association (ERSA), 2006)
This paper explores the implications, from a public sector economics point of view, of combining welfare assessments concerning land use in urban and environmental economics respectively. Urban economics has a long tradition in determining the optimal allocation of land (or space) as a consumption good, while land use issues in environmental economics are predominantly rooted in hedonic pricing as a valuation method for optimising the allocation of public goods. Recently, hedonic pricing methods have been extended by adopting location choice models for the valuation of non-marginal changes in levels of local amenities. Following a possible revision of the location choices by the population, endogenous prices are introduced and compensated for in a willingness to pay. Some of the new methods also allow for social interactions by means of endogenous amenities. While endogenous prices are the main contribution of these so-called sorting models to the valuation literature, until now little attention has been paid to the efficiency of the market equilibrium assumed, in terms of the consumption of space. This is surprising, because social interactions as endogenous amenities might alternatively be interpreted as positive external effects. As such, they are likely to result in an oversupply of land in a competitive market. The dominant characterisation of the equilibrium on the land (or housing) market in sorting models is market clearing, given a fixed supply. In this paper, the total amount of land used in the market clearing equilibrium will be compared with the competitive market equilibrium and the allocation by a benevolent social planner maximising social welfare. It is shown that under relatively general conditions and allowing for endogenous amenities, market clearing with a fixed supply will yield a total amount of land used that is smaller than in a competitive market, but larger than in the case of land use planning. This result suggests that in public policy recommendations, sorting models could benefit from complementing the valuation methodology with the internalisation of external effects for optimising land use.
Keywords: 330